India's Policy Toward Jammu and Kashmir: Understanding the Use of Religious Ideology as a Political Legitimacy - Resen, Putu Titah Kawitri (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
This article aims to analyze the use of religious ideology as political legitimacy in the case of the abrogation of Jammu and Kashmir autonomy by the government of India. The revocation of Articles 370 and 35A of the Indian Constitution terminated the privileges the Jammu and Kashmir region enjoyed for approximately 70 years. The abrogation is viewed as an attempt by the Hindu nationalist government to achieve the Hindutva agenda, Hindu-based ideals. Thus, the research question of this study is developed as follows: How does India’s policy toward Jammu and Kashmir reflect the exercise of religious ideology as a political tool? This study uses the religious legitimacy concept as an analytical framework by exploring and interpreting a range of secondary data sources pertinent to the research question. This study concludes that the ruling party uses Hindutva as a religious ideology by operating the three aspects of religious legitimacy, namely normative, instrumental, and primordial, as justification for its policies towards Jammu and Kashmir. Thus, the Hindu nationalist government accomplished its objectives and garnered people’s support using the three facets of religious legitimacy. Keywords: Jammu Kashmir, Instrumentalism, Normative, Primordialism, Religious ideology Artikel ini bertujuan untuk menganalisis penggunaan ideologi agama sebagai legitimasi politik dalam kasus pencabutan otonomi Jammu dan Kashmir oleh pemerintah India. Pencabutan Pasal 370 dan 35A Konstitusi India mengakhiri hak istimewa yang dinikmati wilayah Jammu dan Kashmir selama kurang lebih 70 tahun. Pencabutan tersebut dipandang sebagai upaya pemerintah nasionalis Hindu untuk mencapai agenda Hindutva, cita-cita berbasis Hindu. Oleh karena itu, pertanyaan penelitian dalam studi ini dirumuskan sebagai berikut: Bagaimana kebijakan India terhadap Jammu dan Kashmir mencerminkan penggunaan ideologi agama sebagai alat legitimasi politik? Penelitian ini menggunakan konsep legitimasi agama sebagai kerangka analisis dengan mengeksplorasi dan menafsirkan berbagai sumber data sekunder yang relevan dengan pertanyaan penelitian. Kajian ini menyimpulkan bahwa partai penguasa menggunakan Hindutva sebagai ideologi keagamaan dengan menjalankan tiga aspek legitimasi agama, yaitu normatif, instrumental, dan primordial, sebagai justifikasi atas kebijakannya terhadap Jammu dan Kashmir. Dengan demikian, pemerintah nasionalis Hindu mencapai tujuannya dan menggalang dukungan masyarakat dengan menggunakan tiga aspek legitimasi agama tersebut. Kata-kata Kunci: Jammu Kashmir, Instrumentalisme, Normatif, Primordialisme, Ideologi keagamaan,